1999
DOI: 10.1001/archneur.56.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The Heidenhain Variant of Creutzfeldt-Jakob Disease

Abstract: The clinical presentation of the Heidenhain variant of CJD was shown to correlate with the neuropathological findings of gliosis and nerve cell loss. In patients with visual disorders of unclear origin and signs of dementia, the differential diagnosis of a Heidenhain variant of CJD must be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 38 publications
3
93
0
16
Order By: Relevance
“…Mutations of the prion protein gene (PRNP) are the cause of familial CJD, which supports the explanatory model of prions as the disease vector [2]. The Heidenhain variant is a rare (< 20%) variant of sporadic Creutzfeldt-Jakob disease (sCJD) in which visual disturbances are the primary presenting symptoms and has more rapid progression [3]. Seventy seven percent of patients with this variant initially present to ophthalmology clinics secondary to these visual symptoms, but have no intraocular findings [4].…”
Section: Introductionmentioning
confidence: 70%
“…Mutations of the prion protein gene (PRNP) are the cause of familial CJD, which supports the explanatory model of prions as the disease vector [2]. The Heidenhain variant is a rare (< 20%) variant of sporadic Creutzfeldt-Jakob disease (sCJD) in which visual disturbances are the primary presenting symptoms and has more rapid progression [3]. Seventy seven percent of patients with this variant initially present to ophthalmology clinics secondary to these visual symptoms, but have no intraocular findings [4].…”
Section: Introductionmentioning
confidence: 70%
“…4 Visual disturbances can include visual misperceptions in terms of size, shape, and color, visual agnosia, visual field defects, cortical blindness with visual anosognosia (Anton syndrome), and visual hallucinations. 5 The histopathologic findings of spongiform degeneration, neuronal loss, and reactive gliosis are most prominent in the occipital lobes. 5 According to the Centers for Disease Control and Prevention diagnostic criteria for CJD, definite sporadic CJD is diagnosed through autopsy.…”
Section: Go To Sectionmentioning
confidence: 99%
“…5 The histopathologic findings of spongiform degeneration, neuronal loss, and reactive gliosis are most prominent in the occipital lobes. 5 According to the Centers for Disease Control and Prevention diagnostic criteria for CJD, definite sporadic CJD is diagnosed through autopsy. Detection of protease-resistant PrPSc in brain tissue is the gold standard for diagnosis of prion disease.…”
Section: Go To Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,10,12,14,24,[26][27][28][29][30]34,55,97,107,108,118,[123][124][125][126] Early studies found that the overall incidence of cortical blindness in CJD was about 13%/-8 but more recent studies suggest that it develops at some stage in the illness in 25-50% of cases? , 1 27, 1 28 Possible reasons for this discrepancy are that patients may deny they are blind (Anton's syndrome)p ,34,60,65, 1 26 or may be too inconsistent to permit accurate assessment of visual fields.68 About 9% of patients are blind at presentation.1 28…”
Section: Cortical Blindnessmentioning
confidence: 99%